The validity of the good spirit, good quality‐of‐life tool for older Aboriginal Australians: Development and validation of cognitive and quality of life assessments for older indigenous peoples internationally. (7th December 2020) - Gilchrist, Lianne; Bessarab, Dawn; Douglas, Harry; LoGiudice, Dina; Ratcliffe, Julie; Flicker, Leon; Hyde, Zoe; Smith, Kate
Abstract: Background: Enhancing quality of life (QoL) is the primary goal of aged care services for older people with dementia. Despite this, there are no culturally appropriate QoL measures for older Indigenous peoples with or without dementia. This study aims to address this gap. Method: The Good Spirit, Good Life (GSGL) tool was co‐developed with older Aboriginal Australians and services in Perth and Melbourne, Australia. Adaptations were made following face validity with Aboriginal participants with dementia or cognitive impairment. Quantitative data collected by Aboriginal researchers included demographic information, GSGL tool (12 items, total score 60), KICA Cog (Indigenous cognitive assessment), EQ‐5D‐5L (health‐related QoL tool), ICECAP‐O (generic wellbeing tool for older people), Geriatric Anxiety Inventory‐Short Form (GAI‐SF), KICA‐Dep (Indigenous depression scale), Aboriginal Resilience and Recovery Questionnaire (ARRQ‐25), and GSGL Carers version. Result: 120 Aboriginal people aged 45‐86 years participated in the GSGL validity study, 68% were women. The mean total GSGL score was 48.7/60. 11% of participants had cognitive impairment or dementia. GSGL internal (Spearman‐Brown 0.83, Cronbach's alpha 0.75) and inter‐rater (ICC 0.69‐0.95) reliability was strong. Concurrent validity is supported by strong correlation with ICECAP‐O (Spearman's Rho (ρ)=0.61, p<0.05). GSGL was weakly correlated with health‐related EQ‐5D‐5L (ρ=‐0.32, p<0.05). Known‐groups validity was supported by significant difference in GSGL scores between participants with (40%) and without anxiety (Student's t test t=4.3, p<0.05) and with (44%) and without depression (t=4.1, p<0.05). GSGL scores did not differ significantly for participants with and without cognitive impairment. Following multivariate regression, resilience (β=0.55, 95%CI [0.39, 0.70]) and GAI‐SF score (β=‐0.22, [‐0.38, ‐0.06]) were associated with total GSGL score. There was significant difference in GSGL item scores (p<0.05; Hotelling's T 2 test), with the 'Country' item having the lowest mean score (3.05/5, p<0.05). Conclusion: The GSGL is a culturally valid tool for measuring quality of life in older Aboriginal Australians. Items are based on the quality of life priorities of Aboriginal Australians with and without dementia. Interventions targeted at building resilience and treating anxiety and depression may improve the quality of life of older Aboriginal Australians. More could be done by services and families to facilitate older people's connection to Country.